Resection and Abdominal Wall Reconstruction for Cesarean Scar Endometriosis - Kento Takaya; Hirokazu Shido; Shun Yamazaki (Case Reports in Medicine)
Introduction. Currently, there are few reports describing the use of reconstructive techniques in the treatment of cesarean scar endometriosis (CSE). Here, we report a case of CSE, a rare form of endometriosis caused by scars from obstetric and gynecological surgeries. Case Report. A 50-year-old woman became aware of a painful, deep scar mass in her lower abdomen during her menstrual period 10 years after her second cesarean section. This was diagnosed as CSE after the biopsy. Under general anesthesia, the mass, a portion of the rectus abdominis, and a 1 cm tumor-free margin were resected as a whole, and the abdominal wall was reconstructed with a soft artificial mesh. Results. No obvious recurrence or subjective symptoms were observed postoperatively or reported in the 1-year follow-up period. Discussion. Endometriosis appearing in a cesarean scar is rare; it is chiefly triggered by intraoperative mechanical implantation. In cases of surgical scar masses with a history of gynecological surgery and associated menstrual symptoms, this syndrome should be considered during diagnosis and treatment.